Field reports, Barb Wilson, fall 1990 - Wilson, Barbara L.et al (1990)
Field reports with detailed bird sighting information and handwritten annotations compiled and submitted by Barb Wilson in a letter to Carl Bendorf on November 29, 1990. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1990. Epson - sheet feed